Rereading Stead’s Grain - Davey, Frank (Studies in Canadian Literature, 1979)
Robert Stead’s novel, Grain, as a textual experience, is extraordinarily ambiguous: at times it provides a strong sense of realism, but it provides so much in addition that realism is in no way its central effect. The "high" narrative language operates as a critique of the characters; it is a language which excludes and judges them. This narrative language draws the reader into an identification with the narrator and not with the characters whom this language appears to invest with realistic detail of action, reflection, and dialogue.